PENGENDALIAN PENGADAAN STRAP DENGAN MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY PADA GUDANG PERUSAHAAN GROUND HANDLING DI BANDARA HALIM PERDANAKUSUMA - Yosi Pahala; Ari Ramadhan; Wynd Rizaldy (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
The purpose of this study is to find out the effectiveness of strap purchase between company system and Economic Order Quantity (EOQ) method. A strap is used to bond a cargo. Each strap has different qualification that depends on the purpose and types of cargo. The problems that happened in ground handling company are strap availability, incompatibility procedure, irregularity strap used, and employees understanding in using strap that they mighthinder airline services. It makes cargo flit hampered and it reduces the strap lifetime since it is damaged due to the ineffective cargo.It happened because the amount of goods loaded into the plane is not appropriate to the kinds of strap used. This study investigated strap procurement in PT Jasa Angkasa Semesta. The method of this study was Economic Order Quantity (EOQ) by comparing the prevailing system. The result shows that the number of economical straps is 208 units each month with the amount of safety stock is 7 units, reorder point id 47 units, and the average of maximum inventory is 215 units each month. The total different of strap provision between company system and EOQ system is Rp. 2674938 (68.12%).